Knowledge, Attitude, and Practice on Cervical Cancer Prevention among Female University Students in AlKharj, Saudi Arabia - Hassanat Ramadan Abdel-Aziz PhD; Nermen Abdelftah Mohamed PhD; Mohamed Gamal Elsehrawy PhD (SAGE Publishing, 2024)
Background Cervical Cancer (CC) is the fourth most frequent malignancy worldwide among females with significant death rates. It ranks as the 8 th most frequent cancer in Saudi female. CC is preventable, with likelihood of full treatment by early detection, because of its long pre-invasive period. Lack of awareness and practice on CC prevention and screening increase the risk of disease. Objective to examine knowledge, attitude, and practice on CC prevention among Saudi female university students. Methods A facility-based cross-sectional study with a convenience sample included 594 female university students studying at health and non-health colleges of Prince Sattam bin Abdulaziz University in Al-Kharj City, Saudi Arabia. All female students were asked to complete an online questionnaire on knowledge, attitude, and practice on CC prevention. Results A total of 594 respondents to the questionnaire, 88.7% of them had unsatisfactory knowledge about CC. Out of a total of 27 points, students' knowledge mean score was 9.3 ± 6.4. Conversely the majority of students (94.4%) had positive attitude toward CC; the mean attitude score was 34.52 ± 5.04 out of 45. Regarding students practice, less than 7% of students were vaccinated against HPV and only 3.7% were screened for cancer cervix. Married females, health colleges students, and high attitude score were significant predictors for the students' knowledge about cancer cervix (P < 0.05). Conclusion Majority of the respondents displayed lack of knowledge; however, they had a positive attitude toward CC. Very alarmingly, almost all of students had inadequate practice regarding CC prevention. So, the study recommends developing and implementing educational programs and strategies for female university students to improve their knowledge and practice related to cervix cancer. Results of this study provide evidence that can help in formulating effective awareness strategies and educational programs for women that would help in CC prevention.